Squamous Cell Carcinoma of the Tongue, the Importance of Early Diagnosis in Danger Zone: A Case Report - Maryam Jalili Sadrabad; Samira Behrad; Shabnam Sohanian (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Oral squamous cell carcinoma is increasing worldwide, especially in developing countries. The etiology of Oral cancer is multifactorial, and most of the cancer deaths can be prevented through lifestyle modifications, early detection and effective treatment. A 27-year-old man who referred to the Oral Medicine Department of Semnan Dental School complaining of redness on his tongue which has been emerged for eight months. Clinical and histopathological examinations have confirmed the diagnosis of oral squamous cell carcinoma (OSCC). Since, the patient didn't have any lymph node involvement, the Clinical stage of OSCC was considered as Stage I. He was treated by an Otorhinolaryngologist and on follow up session the patient declared a chief complaint of a swelling in the sublingual fold which was diagnosed as Ranula. Surgery despite improvements, several functional and aesthetic structures of the oral cavity still sacrifice during the surgical procedures of OSCC. Since the Oral cavity has essential anatomical landmarks and OSCC will bring some morbidity for the patients; therefore, surgical treatment should be carefully considered in the risky anatomical areas of the oral cavity, and it is recommended to be performed by maxillofacial surgeons who are more proficient in oral anatomical landmarks to do not impose any complicate for the patient.